In-situ observation of damage nucleation in graphite under biaxial flexural loading - Mostafavi, M; Duff, J; Marrow, T (2010)
Graphite is used in several designs of nuclear fission reactors (e.g. The Advanced Gas Reactors in the UK, the Pebble Bed Modular Reactor and several high temperature Generation IV designsas neutron moderator and reflectors. In these applications, its structural integrity is important for safe operation. During the reactor lifetime, irradiationinduced dimensional strains and thermal strains may cause significant stresses to develop, and irradiation damage can have a detrimental effect on mechanical properties. Crack nucleation may therefore occur with prolonged operation. One element required for prediction of graphite fracture behaviour under realistic loading conditions is an understanding of the effect of stress state on strength and its statistical distribution. This arises from the statistical sampling and propagation of the inherent defects in the microstructure. Previous work under uniaxial flexure has shown that the digital image correlation technique, which measures surface displacements with high precision, can be used to monitor the nucleation and growth of these defects. This provides an insight into the variability of strength. In this study a biaxial ring-on-ring flexural test rig has been developed and crack nucleation and propagation have been studied using digital image correlation. Comparison is made between the fracture behaviour of graphite in biaxial loading condition with the uniaxial four-point-bend loading. A reduction of 17% in the mean strength was observed as the loading condition was changed from uniaxial to equi-biaxial.